OP0134 Risk stratification in patients with undifferentiated arthritis according to the 2010 ACR/EULAR criteria. (23rd January 2014) - Krabben, A.; Abhishek, A.; Britsemmer, K.; Filer, A.; Huizinga, T.W.J.; Raza, K.; van Schaardenburg, D.; van der Helm-van Mil, A.H.M.
Abstract : Background: Early recognition and treatment of Rheumatoid Arthritis (RA) is associated with an improved outcome. The 2010 ACR/EULAR criteria for RA identify RA patients earlier than the 1987 criteria. Nevertheless, we observed that 24% of the 2010-undifferentiated arthritis (UA) patients develop RA during follow-up. Objectives: Here we studied this frequency in other cohorts and evaluated the prognostic accuracy of anti-CCP antibodies and the Leiden prediction rule in 2010-UA patients. Methods: 2010-UA patients derived from three Early Arthritis Clinics were studied: 776 UA patients from Leiden, 121 from Birmingham and 322 from Amsterdam. Fulfilling the 1987 ACR criteria for RA during follow-up was studied as outcome. The presence of anti-CCP antibodies and the prediction score at baseline were evaluated in relation to the outcome. Results: In the three cohorts, 24%, 26% and 12% of the 2010-UA patients fulfilled the 1987 criteria after one year, respectively. Some of these patients fulfilled the 1987 criteria already at baseline. In "1987-and-2010-UA patients'', 15%, 21% and 9% respectively developed RA. In all cohorts, the large majority of 2010-UA patients were anti-CCP negative and had low prediction scores at baseline. Therefore these markers were not helpful for risk stratification. Conclusions: Some of the 2010-UA patients progress to RA. Anti-CCP antibodies and the Leiden prediction rule are not useful to identify these patients. Hence, other prognostic markers are needed with significantly different sensitivity and specificity characteristics to clinical examination; these may include imaging modalities such as ultrasound or extremity-MRI. Disclosure of Interest: None Declared